Metagenomic analysis reveals mixed Mycobacterium tuberculosis infection in a 18th century Hungarian midwife. (December 2022) - Jäger, Heidi Y.; Maixner, Frank; Pap, Ildikó; Szikossy, Ildikó; Pálfi, György; Zink, Albert R.
Abstract: The Vác Mummy Collection comprises 265 well documented mummified individuals from the late 16th to the early 18th century that were discovered in 1994 inside a crypt in Vác, Hungary. This collection offers a unique opportunity to study the relationship between humans and pathogens in the pre-antibiotic era, as previous studies have shown a high proportion of tuberculosis (TB) infections among the individuals. In this study, we recovered ancient DNA with shotgun sequencing from a rib bone sample of a 18th century midwife. This individual is part of the collection and shows clear skeletal changes that are associated with tuberculosis and syphilis. To provide molecular proof, we applied a metagenomic approach to screen for ancient pathogen DNA. While we were unsuccessful to recover any ancient Treponema pallidum DNA, we retrieved high coverage ancient TB DNA and identified a mixed infection with two distinct TB strains by detailed single-nucleotide polymorphism and phylogenetic analysis. Thereby, we have obtained comprehensive results demonstrating the long-time prevalence of mixed infections with the sublineages L4.1.2.1/Haarlem and L4.10/PGG3 within the local community in preindustrial Hungary and put them in context of sociohistorical factors.